Research Note: College Students' Attitudes toward Christianity in Xi'an, China - Wang, Chao (Religions, 2016)
Atheism is the mainstream belief system in contemporary China. In recent years, a growing number of Chinese have converted to different religions, particularly Christianity. In this study, we conducted a survey in the region of Xi'an to investigate the following three questions: How common is Christianity among college students in Xi'an? How many of them have converted to the Christian faith? How do they gain their knowledge of Christianity? It is a popular notion in China that many college students have, in recent times, converted to Christianity. However, our survey results do not provide support for this. While many students encounter Christian faith on university campuses, especially through organizations such as The Fellowship, students in this survey report low religious affiliation.